Silicon: A neglected micronutrient essential for bone health. Issue 13 (July 2021) - Rondanelli, Mariangela; Faliva, Milena A; Peroni, Gabriella; Gasparri, Clara; Perna, Simone; Riva, Antonella; Petrangolini, Giovanna; Tartara, Alice
Bone matrix is predominantly made up of collagen, and in vitro and in animal models studies have shown that silicon is linked to glycosaminoglycans and plays an important role in the formation of cross-links between collagen and proteoglycans, determining the beneficial effects on strength, composition, and mechanical properties of bone. However, there are still no precise indications regarding a possible role of silicon on bone health in humans. Given this background, the aim of this narrative review was to consider the effectiveness of silicon dietary intake and silicon dietary supplementation (alone or with other micronutrients), in order to suggest a daily dosage of Si supplementation, on bone mineral density in humans. This review included eight eligible studies: four regarding dietary intake and four considering supplementation with silicon alone or with other nutrients. Despite the number of studies considered being low, the number of subjects studied is high (10012) and the results are interesting. Although to date the available scientific evidences are not considered valid enough to allow to establish an adequate level of Silicon intake, based on extrapolations from the data obtained with studies on animal and human models, it has been suggested that an adequate intake in order to promote beneficial effects for bone could be considered to be around 25 mg silicon/day. As for silicon dietary supplements, it has been shown that the combined treatment with orthosilicic acid (6 mg), calcium, and vitamin D has a potentially beneficial effect on femoral BMD compared to only use of calcium and vitamin D.